InOx Doped SnO2 Nanostructure Deposited on MEMS Device by PE-ALD Process for Detection of NO2. Issue 2 (1st February 2023) - Shi, Zhong-Hong; Hsiao, Yu-Jen; Wang, Sheng-Chang; Tien, Wei-Chen
Abstract : The micro-electro-mechanical systems (MEMS) method makes the gas sensing element. The sensing layer uses RF Sputter and plasma-enhanced atomic layer deposition (PE-ALD) technology to deposit indium oxide (InOx) thin films on Tin oxide (SnO2 ) to form an n-n type double-layer structure. The results show that the response of SnO2 -InOx and monolayer SnO2 is 153% and 55%, respectively, which is an improvement of 98% under exposure to 0.6 ppm NO2, and the sensor can obtain the best sensing at 200 °C (∼14 mW). In response, the lowest NO2 concentration was 0.2 ppm, and the selectivity test was carried out with four other gases, such as SO2, H2, CO, and NH3, and the test results showed the specificity for NO2 .